2020
DOI: 10.3390/cells9030750
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Endoplasmic Reticulum Stress in Intracerebral Hemorrhage

Abstract: The endoplasmic reticulum (ER) is an intracellular organelle that performs multiple functions, such as lipid biosynthesis, protein folding, and maintaining intracellular calcium homeostasis. Thus, conditions wherein the ER is unable to fold proteins is defined as ER stress, and an inbuilt quality control mechanism, called the unfolded protein response (UPR), is activated during ER stress, which serves as a recovery system that inhibits protein synthesis. Further, based on the severity of ER stress, the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 123 publications
(135 reference statements)
0
26
0
Order By: Relevance
“…The Blue module, positively correlated with rPHE, was overrepresented by major protein translation, stress response, and cell death pathways, including Eukaryotic Initiation Factor (EIF), p70S6K, mTOR, Nucleotide Excision Repair (NER), protein ubiquitination, Unfolded Protein Response (UPR), Endoplasmic Reticulum Stress Pathway, and Necroptosis Signaling (Fig. 5 f, Table S2 O)—many of which have been implicated in ICH [ 97 ]. The inability to properly fold proteins leads to UPR and often programmed cell death including necroptosis [ 65 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Blue module, positively correlated with rPHE, was overrepresented by major protein translation, stress response, and cell death pathways, including Eukaryotic Initiation Factor (EIF), p70S6K, mTOR, Nucleotide Excision Repair (NER), protein ubiquitination, Unfolded Protein Response (UPR), Endoplasmic Reticulum Stress Pathway, and Necroptosis Signaling (Fig. 5 f, Table S2 O)—many of which have been implicated in ICH [ 97 ]. The inability to properly fold proteins leads to UPR and often programmed cell death including necroptosis [ 65 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged environmental stress triggers signal transduction pathways that lead to apoptosis and thereby heighten pathological processes, leading to cerebral damage (Chi et al, 2019 ). Endoplasmic reticulum stress exerts its vital role in stroke-induced neural apoptosis (Mohammed Thangameeran et al, 2020 ) through activation of downstream CCAATenhancer-binding protein homologous protein (CHOP) and caspase-12 (Chi et al, 2019 ; Chu et al, 2019 ; Li Y. et al, 2020 ). SIRT1 is a nicotine adenine dinucleotide (NAD+)-dependent enzyme that deacetylates numerous transcription factors in response to ischemic stress and is involved in various biological pathways (Chen et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had indicated that autophagy, ER stress and apoptosis were involved in various physiological and pathological conditions in stroke, especially in intracerebral hemorrhage ( Durocher et al, 2019 ; Mohammed Thangameeran et al, 2020 ; Yang et al, 2018 ). HERP has been described as a ubiquitin-like membrane protein induced by endoplasmic reticulum stress, however, whether HERP plays a positive or negative role in the intracerebral hemorrhage remains controversial and the role of HERP in the autophagy, ER stress, apoptosis is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A number of works in recent years indicate that the pathological process of ICH is complex, including brain edema, hematoma formation, and the activation of cytotoxic, inflammatory, oxidative, autophagy and endoplasmic reticulum (ER) stress pathways. Therefore, it is necessary to elucidate these cellular and molecular mechanisms of ICH ( Li et al, 2020 ; Mohammed Thangameeran et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%